Ultrasound scoring system for prenatal diagnosis of placenta accreta spectrum - Junling Zhang; Hezhou Li; Demin Feng; Juan Wu; Zhaoyu Wang; Fan Feng (BMC Pregnancy and Childbirth, 2023)
Abstract Background To develop an ultrasound scoring system for placenta accreta spectrum (PAS), evaluate its diagnostic value, and provide a practical approach to prenatal diagnosis of PAS. Methods A total of 532 pregnant women (n = 184 no PAS, n = 120 placenta accreta, n = 189 placenta increta, n = 39 placenta percreta) at high-risk for placenta accreta who delivered in the Third Affiliated Hospital of Zhengzhou University between January 2021 and December 2022 underwent prenatal ultrasound to evaluate placental invasion. An ultrasound scoring system that included placental and cervical morphology and history of cesarean section was created. Each feature was assigned a score of 0 ~ 2, according to severity. Thresholds for the total ultrasound score that discriminated between no PAS, placenta accreta, placenta increta, and placenta percreta were calculated. Results Univariate and multivariate regression analysis identified seven indicators of PAS that were included in the ultrasound scoring system, including placental location, placental thickness, presence/absence of the retroplacental space, thickness of the retroplacental myometrium, presence/absence of placental lacunae, retroplacental myometrial blood flow and history of cesarean section. Using the final ultrasound scoring system, no PAS is diagnosed at a total score < 5, placenta accreta or placenta increta is diagnosed at a total score 5–10, and placenta percreta is diagnosed at a total score ≥ 10. Conclusions This study identified seven indicators of PAS and included them in an ultrasound scoring system that has good diagnostic efficacy and clinical utility. Trial registration ChiCTR2300069261 (retrospectively registered on 10/03/2023).